Branched-Chain Amino Acids Exacerbate Obesity-Related Hepatic Glucose and Lipid Metabolic Disorders via Attenuating Akt2 Signaling - Zhao, Huishou; Zhang, Fuyang; Sun, Dan; Wang, Xiong; Zhang, Xiaomeng; Zhang, Jinglong; Yan, Feng; Huang, Chong; Xie, Huaning; Lin, Chen; Liu, Yi; Fan, Miaomiao; et al. (Diabetes (New York, N.Y.), 2020)
Branched chain amino acids (BCAAs) are associated with the progression of obesity-related metabolic disorders, including type 2 diabetes and nonalcoholic fatty liver disease. However, whether BCAAs disrupt the homeostasis of hepatic glucose and lipid metabolism remains unknown. In this study, we observed that BCAAs supplementation significantly reduced high-fat (HF) diet–induced hepatic lipid accumulation while increasing the plasma lipid levels and promoting muscular and renal lipid accumulation. Further studies demonstrated that BCAAs supplementation significantly increased hepatic gluconeogenesis and suppressed hepatic lipogenesis in HF diet-induced obese (DIO) mice. These phenotypes resulted from severe attenuation of Akt2 signaling via mTORC1- and mTORC2-dependent pathways. BCAAs/branched-chain α-keto acids (BCKAs) chronically suppressed Akt2 activation through mTORC1 and mTORC2 signaling and promoted Akt2 ubiquitin-proteasome–dependent degradation through the mTORC2 pathway. Moreover, the E3 ligase Mul1 played an essential role in BCAAs/BCKAs-mTORC2-induced Akt2 ubiquitin-dependent degradation. We also demonstrated that BCAAs inhibited hepatic lipogenesis by blocking Akt2/SREBP1/INSIG2a signaling and increased hepatic glycogenesis by regulating Akt2/Foxo1 signaling. Collectively, these data demonstrate that in DIO mice, BCAAs supplementation resulted in serious hepatic metabolic disorder and severe liver insulin resistance: insulin failed to not only suppress gluconeogenesis but also activate lipogenesis. Intervening BCAA metabolism is a potential therapeutic target for severe insulin-resistant disease.